PENGARUH TINGKAT PENDAPATAN TERHADAP TINGKAT KONSUMSI PETANI KARET DI DESA MUARA MUSU KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Samsiah, Samsiah; Johan, Rina Selva; RM Riadi, RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Consumption expenditure as a function of incomeis a huge factor influence on the behavior of rubber farmers in making consumption. Therefore, the need to increase the maximum income, high-low due to the rubber farmers' income effect on consumption levels. The purpose of this study was to determine the pattern of consumption of rubber farmers and to determine the effect of earned income on the consumption patterns of rubber farmers. The sample in this study was 63 rubber farmers, who analyzed and descriptive kuantitatif lenear simple regression methods based on the theory ofthe consumption function. The results of the study, showed the rubber farmers' income used to meet consumption needs, such as children's education, medical expenses, transportation costs and other costs. 67.4% of consumption is influenced by income. 41.1% of food consumption is influenced by income. 62.3% of non-food consumption is affected by income and the rest is influenced by other things. Changes in income has the effect of 0.802% on the consumption behavior.  Keywords: income, consumption.